Efektivitas Sterilisasi Metode Panas Kering pada Alat Medis Ruang Perawatan Luka Rumah Sakit dr. H. Soemarno Sosroatmodjo Kuala Kapuas - Raudah Raudah; Tien Zubaidah; Imam Santoso (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2017)
Abstract: Effectiveness Of Sterilization Method Of Dry Heat At The Wound Care Medical Devices Hospital Room Dr. H. Soemarno Sosroatmodjo Kuala Kapuas. Hospital Dr. H. Soemarno Sosroatmodjo is a Type C hospitals that provide 24-hour medical services.Bed capacity of 145 with the number BOR (Bed Occupancy Rate) 51.36%.Efforts to prevent the occurrence of nosocomial infections from medical devices one of which is the process of sterilization with dry heat heating process.The purpose of this study was to determine the effectiveness of dry heat sterilization methods on medical devices in the Hospital Dr. H. Soemarno Sosroatmodjo. This type of research is quasi-experimental.Type variables used are the independent variables (temperature variation with the dry heat oven), the dependent variable (number of bacteria).Samples taken medication is a tool set consisting of a pair of tweezers and tub instruments. Analysis of data use Oneway Anova test. Based on the results of the examination, in the highest number of bacteria known medical tool tweezers is the average number of bacteria colonies 1.33 / cm at 125oC, and the highest number of bacteria of medical tools like instrument that is the average number of bacteria colonies 0.66 / cm at the temperature of 125oC. Statistical data analysis for medical devices tweezers with Oneway Anova test, after sterilized generate significant value of 0.09, which sig> 0.05 so that Ho is accepted, meaning there is no significant difference and statistical analysis for medical devices like instrument with Oneway Anova test produces the significant value of 0.40, which sig> 0.05 means that there is no significant difference. Keywords: Hospitals; medical device; numbers germs; sterilization.